Parent–child shared book reading challenges and facilitators: a systematic review and meta synthesis - Nan, Jiaopeng; Tian, Yin (Frontiers in Psychology, 2025)
BackgroundParent–child shared book reading is a foundational activity that supports children’s literacy development, including language skills, cognitive growth, and social–emotional competencies. Despite its recognized benefits, various factors influence the consistency and quality of shared reading practices across different families and communities. This meta-synthesis aimed to comprehensively explore Parent–child shared book reading challenges and facilitators, drawing on qualitative research evidence.MethodsA systematic search of nine electronic databases (PubMed, Web of Science, Scopus, Medline, Embase, ScienceDirect, CINAHL, PsycINFO, and Google Scholar) was conducted in January 2025. Inclusion criteria focused on qualitative studies examining parent–child shared reading experiences among families with children under 18 years old. Studies were appraised for methodological quality using the Critical Appraisal Skills Program (CASP) checklist. Data from selected studies were extracted and analyzed using thematic synthesis, with an inductive coding process conducted through MAXQDA 24 software.ResultsThe analysis identified two main categories—facilitators and challenges—with ten first and 31 s categories. Facilitators included enhancing access to books and reading opportunities, providing parental support and education, creating positive and enjoyable reading experiences, ensuring high-quality book content, fostering child development through moral, social, and cognitive learning, and strengthening parental motivation. Challenges encompassed limited resources and access, sociocultural and parental barriers such as time constraints and mental health difficulties, gaps in parental knowledge and skills, and engagement challenges related to child readiness and the use of digital books. The synthesis highlighted the dynamic interplay between individual, family, and environmental factors influencing shared reading practices.ConclusionParent–child shared book reading is a complex, dynamic practice influenced by social, cultural, and psychological factors. Strengthening access to books, supporting parents with targeted education, and fostering enjoyable reading experiences can significantly enhance shared reading practices. Future studies should broaden cultural representation, explore digital formats, and address parental mental health to develop effective, inclusive strategies that promote early literacy and strong parent–child bonds.